2016
DOI: 10.3168/jds.2015-9805
|View full text |Cite
|
Sign up to set email alerts
|

Circulating amino acids in blood plasma during the peripartal period in dairy cows with different liver functionality index

Abstract: The liver functionality index (LFI) measures the changes of albumin, cholesterol, and bilirubin concentrations between 3 and 28 d postpartum. This composite index, based on variables with direct relevance to liver-specific plasma protein synthesis (albumin), hepatic/intestinal lipoprotein synthesis (cholesterol), and clearance of breakdown products of heme catabolism (bilirubin), provides a tool for evaluating manifestations of hepatic disease. Both energy and protein metabolism are likely to be affected by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 41 publications
6
57
1
1
Order By: Relevance
“…In addition, rodent research revealed that limiting MET and CHOL in ketogenic diets increased expression of fatty acid oxidation and inflammatory genes, supporting a potential role of MET and CHOL supplementation on ketosisrelated inflammation (Pissios et al, 2013). In agreement with this, MET-supplemented cows experienced fewer cases of ketosis and had greater plasma concentrations of albumin, cholesterol (index of lipoproteins) and lower haptoglobin (Zhou et al, 2016a, Zhou et al, 2016c, suggesting MET supplementation had direct bearing on the lower inflammatory status in HLFI cows. In contrast, CHOL supplementation was not associated with changes in the incidence of ketosis or plasma albumin, cholesterol, and haptoglobin concentrations.…”
Section: Inflammation and Oxidative Stress In Cows With Hlfi And Llfimentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, rodent research revealed that limiting MET and CHOL in ketogenic diets increased expression of fatty acid oxidation and inflammatory genes, supporting a potential role of MET and CHOL supplementation on ketosisrelated inflammation (Pissios et al, 2013). In agreement with this, MET-supplemented cows experienced fewer cases of ketosis and had greater plasma concentrations of albumin, cholesterol (index of lipoproteins) and lower haptoglobin (Zhou et al, 2016a, Zhou et al, 2016c, suggesting MET supplementation had direct bearing on the lower inflammatory status in HLFI cows. In contrast, CHOL supplementation was not associated with changes in the incidence of ketosis or plasma albumin, cholesterol, and haptoglobin concentrations.…”
Section: Inflammation and Oxidative Stress In Cows With Hlfi And Llfimentioning
confidence: 58%
“…The fact that supplementation of carnosine in nonruminants was able to rescue prooxidant-antioxidant balance by restoring depleted levels of blood GSH and activities of antioxidant enzymes (Aydin et al, 2010) indicates the potential decrease in circulating carnosine in events of oxidative stress. Although the contribution of carnosine to restore prooxidant-antioxidant balance under physiologic (without carnosine supplementation) conditions remains unknown, the overall greater circulating carnosine together with greater circulating taurine as well as hepatic GSH reported previously (Zhou et al, 2016a) indicate a less pronounced oxidative stress status in response to periparturient MET supplementation.…”
Section: Aa Derivativesmentioning
confidence: 93%
See 1 more Smart Citation
“…The main affected gene (FC < −3, Additional file 8: Table S5) for both the catabolic and anabolic branches of the BCAA pathway at 7 d postpartum was BCAT1 (Branched Chain Amino-Acid Transaminase 1, Cytosolic), which can catalyze both the deamination and amination of BCAA and related keto-acids. Recently, a higher postpartum plasma concentration of BCAA (specifically Val and Iso) in TMR-fed dairy cows was linked to greater liver function and a possible better responsiveness of the immune system [68]. In the present study, plasma AA data were not collected, but it is plausible that an increase in hepatic BCAA biosynthesis in B5F75 cows led to similar results, indicating how feed restriction would be more appropriate for optimally-conditioned cows.…”
Section: Resultsmentioning
confidence: 74%
“…Nestas condições de sobrecarga hepática, o fígado modifica seu padrão normal de síntese, tornando-se menos eficiente metabolicamente (Bobe et al 2004), por isso alternativas que melhorem a funcionalidade hepática poderiam garantir uma melhor perfomance do fígado para enfrentar os desafios do pós-parto. O índice de funcionalidade hepática (IFH) permite uma avaliação do organismo da vaca ao final do primeiro mês de lactação (Bertoni & Trevisi 2013;Zhou et al, 2016Zhou et al, e 2017 e tem sido utilizado para caracterizar a gravidade do estado inflamatório que os animais enfrentam nesse período. Sua determinação considera níveis séricos de três metabólitos hepáticos, albumina, colesterol e bilirrubina.…”
Section: Introductionunclassified